2011
DOI: 10.1176/ps.62.8.pss6208_0878
|View full text |Cite
|
Sign up to set email alerts
|

Who Is Paying the Price? Loss of Health Insurance Coverage Early in Psychosis

Abstract: Objective Discontinuities in health insurance coverage may make it difficult for individuals early in psychosis to receive the services that are critical in determining long-term outcome. This study reports on the rates and continuity of insurance coverage among a cohort of early-psychosis patients enrolled in Specialized Treatment Early in Psychosis (STEP) at the Connecticut Mental Health Center. Methods Insurance status at baseline, six months, and 12 months was collected from 82 participants from a combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…STEP recently completed the first U.S. randomized controlled trial to determine the feasibility and effectiveness of this public-sector based approach to FES [ 18 ]. This trial has also collected detailed information on sources of direct and indirect cost [ 20 22 ] that support international data on the health economic benefits of FES.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…STEP recently completed the first U.S. randomized controlled trial to determine the feasibility and effectiveness of this public-sector based approach to FES [ 18 ]. This trial has also collected detailed information on sources of direct and indirect cost [ 20 22 ] that support international data on the health economic benefits of FES.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the anticipated but unclear changes in U.S. pathways over time (e.g. with ongoing reforms in access to health insurance [ 22 ]) make it vital to test any ED strategy against a control setting to disentangle the effects of an ED campaign from secular changes in the U.S. healthcare environment. Finally, FES care is a rarity in most U.S. settings and can reduce DUP in a region simply by its presence.…”
Section: Introductionmentioning
confidence: 99%
“…In latter systems, such as in the U.S., strong incentives exist to shift costs between different payers with measurably adverse outcomes for patients and their families early in the course of psychotic illnesses. [83]. Also, service utilization patterns and the costs associated with them can vary between sites and across countries.…”
Section: Are Ei Services Worth the Cost?mentioning
confidence: 99%
“…Privately insured patients struggling with the emergence of a serious mental illness can rapidly lose health insurance [83] and typically arrive at the public state mental health system long after the critical period for early intervention has elapsed.…”
Section: Is Early Intervention Feasible?mentioning
confidence: 99%
“…Prior research has found that individuals with serious mental illness experience frequent insurance disruptions 22 24 , and individuals with schizophrenia are more likely to experience an insurance disruption – often a coverage gap – compared to other types of serious mental illness 25 . However, most studies examining insurance stability for those with schizophrenia were conducted before the ACA, limited to those with either first episode psychosis or first diagnosis of schizophrenia, or limited to young adults 22 24 .…”
Section: Introductionmentioning
confidence: 99%